A Case of Histoplasma capsulatum Causing Granulomatous Liver Disease and Addisonian Crisis. (1st October 2001) - Wong, P; Houston, S; Power, B; Lalor, E; Bain, VG
Abstract : A 56-year-old man with persistently elevated liver enzyme levels, fatigue, lethargy and a 9.0 kg weight loss over six months underwent a percutaneous liver biopsy that demonstrated multiple granulomas. Screening serologies were positive for histoplasmosis, and he was started on itraconazole treatment. He returned to hospital the same night with coffee-ground emesis and in Addisonian crisis requiring parenteral steroids and intensive care unit support. An abdominal computed tomography scan revealed bilaterally enlarged, nonenhancing adrenal glands suggestive of infarcts, presumed secondary to histoplasmosis. Treatment was initiated with amphotericin B, and Histoplasma capsulatum was cultured from his urine and cerebrospinal fluid. A serum immunodiffusion test was also positive for both H and M bands, indicating active infection with Histoplasmosis species. His serum and urine samples were also weakly positive for the antigen. Despite complications of renal failure, pneumonia and congestive heart failure, he recovered with medical therapy and was discharged home to complete a prolonged course of itraconazole therapy. While hepatic granulomas often reflect an occult disease process, the cause may remain undiscovered in 30% to 50% of patients despite exhaustive investigations. H capsulatum is an uncommon cause of granulomatous liver disease, and with its protean clinical presentation, a high index of suspicion is needed to make the diagnosis and avoid the potentially high fatality rate associated with disseminated infection.